Attitudes of referees in a multidisciplinary journal: An empirical analysis. (15th April 2016) - Casnici, Niccolò; Grimaldo, Francisco; Gilbert, Nigel; Squazzoni, Flaminio
Abstract : This paper looks at 10 years of reviews in a multidisciplinary journal, The Journal of Artificial Societies and Social Simulation (JASSS), which is the flagship journal of social simulation. We measured referee behavior and referees' agreement. We found that the disciplinary background and the academic status of the referee have an influence on the report time, the type of recommendation and the acceptance of the reviewing task. Referees from the humanities tend to be more generous in their recommendations than other referees, especially economists and environmental scientists. Second, we found that senior researchers are harsher in their judgments than junior researchers, and the latter accept requests to review more often and are faster in reporting. Finally, we found that articles that had been refereed and recommended for publication by a multidisciplinary set of referees were subsequently more likely to receive citations than those that had been reviewed by referees from the same discipline. Our results show that common standards of evaluation can be established even in multidisciplinary communities.